Production Engineering and Robust Control - Tolouei-Rad, Majid; Li, Pengzhong; Luo, Liang (IntechOpen, 2022)
Production engineering and advanced control systems make it possible to respond to the increasing needs of nations around the world. This book presents some of the new ideas, creative applications, and process optimization methods for more efficient utilization of resources available for improving productivity and reliability or lessening the times and costs of industrial production processes. It presents a variety of chapters on the development of production techniques and systems including abrasive waterjet machining, additive manufacturing, and production management. It also discusses the methods used for the development and improvement of control mechanisms with the objective of improving the reliability and efficiency of production systems. This book is useful for researchers, engineers, and experts working in different areas of production engineering and manufacturing control systems.